Antiviral activity of macrophage‐activating Chinese mixed herb hot water extract. Issue 1 (6th November 2017) - Yoshida, Yoshihiro; Tsukamoto, Mayu; Muraoka, Ken‐ichi; Yoshida, Satoshi; Shiraki, Kimiyasu
ABSTRACT: Aim: Macrophage‐activating Chinese mixed herb (MACH) extract, a hot‐water decoction of Cucurbita moschata (pumpkin seed), Carthamus tinctorius (safflower flower), P. asiatica (psyllium seed), and L. japonica (Japanese honeysuckle flower), is able to induce the production of interferon and interleukin, and hence reduce viral load in patients with hepatitis C virus (HCV) infection. The aim of this study was therefore to analyze the antiviral activity in the available models and identify the mechanism of alleviation of HCV infection. Methods: The antiviral and anti‐Herpes simplex virus (anti‐HSV) activity of MACH extracts was examined using the plaque reduction assay in a mouse model of cutaneous HSV infection. Results: MACH extracts inhibited plaque formation of HSV, Varicella zoster virus, cytomegalovirus, and poliovirus at 50% effective concentration for plaque formation (EC50 ) of 3.09, 0.84, 1.54, and 3.3 mg/mL, respectively. MACH extract inhibited the late protein synthesis of HSV, indicating inhibition of viral DNA synthesis. MACH extract was given orally at 0, 40, and 400 mg in 200 μL water 7 days before infection in female BALB/c mice (6 weeks old) cutaneously infected with HSV. MACH extract was not toxic, as assessed by bodyweight changes, and significantly alleviated the development of skin lesions at days 6–8 ( P < 0.05) but did not prolong the survival period. Conclusion: On plaque reduction assay, MACH extract had significant but mild therapeutic anti‐HSV activity. This anti‐viral activity might be associated with the therapeutic antiviral activity in animals and humans.